Qualidade da água subterrânea e a presença de Nitrato na zona urbana de Croatá, Estado do Ceará - Alves, Otaciana Ribeiro (2014)
The study was conducted in the city of Croatá, Ceará, which population is 17,069 inhabitants, water supplied by drilling wells. The coverage ratio of sewage is 33.5 %, with only 17.3% of the links connected to the sewage network. In the study area, the prevailing hydrogeological formation is the Serra Grande Aquifer. The survey aimed as main target, to assess the quality of groundwater, of the City of Croatá, Ceará focusing primarily the results to determine the concentrations of nitrate in the groundwater, by the analytical methodology of the Column Cadmium - Copper Reducing the “Standard Methods for the Examination of Water and Wastewater”. 25 sampling points distributed around the city were selected getting the confirmation of the presence of nitrate ranging from 0.06 to 48.1 mg/L NO3 N. According to the Nº 2914/11 ordinance of the Ministry of Health,which sets standards of drinking water for human consumption, the maximum allowed value of nitrate in samples is 10 mg/L NO3 N. The results showed that 62.64 % of the samples have concentrations above 10 mg/L NO3 N, indicating a contamination of the aquifer by sewage, garbage, or other waste with rich organic matter in the urban area of the study. From the 11 samples analyzed outside the urban perimeter, all results were below 10 mg/L NO3, meeting the standards for human consumption. This study recommends that all the drilling wells of the urban perimeter of the city to be monitored in water quality parameter, as well as to dig new wells in the free zone of contamination, treat the water with nitrate levels above the required in the ordinance and prepare didactic materials, booklets and pamphlets, educating people about polluted waters and the health risks involved.